Model of Premarried Sexual Behavior in Adolescent City of Medan in 2021 Using Logistic Regression - Rada Mazly (JMEA : Journal of Mathematics Education and Application, 2023)
In this study, the problem taken was premarital sexual behavior in adolescents in Medan City in 2021, by looking at the shift in the norms of right and wrong, good and bad, especially in the context of sexual behavior becoming increasingly real. The purpose of this study is to determine a model of premarital sexual behavior in adolescents in Medan City in 2021 by using logistic regression to carry out a prevention by looking at what variable factors have a significant relationship to the level of premarital sexual behavior that occurs in Medan City. In this study, there were 100 samples that had been taken using Cluster Random Sampling with four predictor variables, namely media, attitudes, knowledge and parental roles and the response variable, namely premarital sexual behavior in adolescents. Based on binary logistic regression, the model obtained is with the smallest G test value and each model on multiple variables, it can be seen that the entire value of Cox Snell and Nagelkerke (R2) 0.50 in the overall parameter significance test which states that the level of effective contribution given by each predictor variable to the response variable has not enough to be used as a model of premarital sexual behavior in adolescents in Medan City in 2021. This means that there are other variables besides media, knowledge, attitudes and parental roles that can affect the level of premarital sexual behavior in adolescents in Medan City in 2021